Novel Coronavirus Disease (COVID-19): An Update - Nayak, Niranjan; Rai, SK (Nepal Medical College Journal, 2020)
At present, a novel Corona Virus called Severe Acute Respiratory Syndrome corona virus (SARS-Cov-2) has caused pandemic infection. This virus has been thought to be of zoonotic origin specially originating from bats. This Virus originated from wet market in Wuhan, China in December 2019. A small cluster of Pneumonia cases that occured in Wuhan in December 2019 was named COVID-19 (Corona Virus Disease) by World Health Organization (WHO). The Covid-19 is still on the rise across the globe. As there is no treatment available for the SARS-Cov-2, it is important to mantain social distance, practice frequent hand-washing and use mask.